Molecular Binding Interactions: Their Estimation and Rationalization in QSARs in Terms of Theoretically Derived Parameters - David F.V. Lewis; Howard B. Broughton (The Scientific World Journal)
An extensive survey of molecular binding interactions and parameters used in QSARs is reported, which includes consideration of lipophilicity and the derivation of Linear Free Energy Relationships associated with drug-receptor binding, together with an overview of the various contributions to binding energy. The lipophilic parameter, log P, and its relevance to desolvation energy is outlined and explanation of the parameters derived from electronic structure calculation is provided, leading into a summary of molecular dynamics simulations.